Nitric oxide synthase 1 as a potential modifier gene of decline in lung function in patients with cystic fibrosis - Texereau, J; Marullo, S; Hubert, D; Coste, J; Dusser, D J; Dall’Ava-Santucci, J; Dinh-Xuan, A T (Thorax, 2004)
Background: The severity of lung disease varies widely in patients with cystic fibrosis (CF) who have the same type of mutations of the cystic fibrosis transmembrane regulator (CFTR) gene, suggesting involvement of “modifier” genes. The nitric oxide synthase 1 (NOS1) gene is a candidate for this role because exhaled nitric oxide (NO) is reduced in patients with CF and NOS1 activity contributes to transepithelial ionic transport, immune defence, and non-specific inflammation of the airways. Methods: Dinucleotide GT repeat polymorphism was studied in the 5′ untranslated region of the NOS1 gene, immediately upstream from the transcription initiation site, in 59 patients with CF and 59 healthy controls. Results: Nineteen alleles of the NOS1 gene were identified according to the number of GT repeats (from 18 to 36) in the 5 untranslated region. Exhaled NO levels were significantly correlated with the number of GT repeats. Patients with CF who had the NOS1 genotype associated with high NO production had a slower decline in lung function during the 5 year follow up period. There was no confounding effect of age, chronic bacterial colonisation of the airway, or CFTR genotype. Conclusions: These data suggest a possible link between the NOS1 gene locus and the rate of decline in lung function in patients with CF.